0279 Fatigue and Pain Responses Across Repeated Exposure to Experimentally Induced Sleep Disturbance and Intermittent Recovery Sleep: Sex Differences. (27th May 2020) - Goldstein, M R; Simpson, N S; Devine, J K; Dang, R; Connors, C; Engert, L C; Chatterton, B; Scott-Sutherland, J; Yang, H; Mullington, J M; Haack, M
Abstract: Introduction: Sleep disturbances are more common in women than in men, as are many chronic pain disorders characterized by inflammation and fatigue. This study investigated sex differences in fatigue and pain responses to sleep disruption and whether such responses recover with uninterrupted sleep. Methods: 24 healthy young individuals (12 women; ages 18–42 yrs) participated in a study consisting of two counterbalanced 19-day experimental in-hospital stays, separated by two months. Following 3 baseline nights, participants were exposed to 3 nights of sleep disruption (SD) involving delayed sleep onset, hourly awakenings, and early-morning awakenings without return to sleep, followed by 1 night of recovery sleep. This 4-day cycle was repeated three times and finished with 3 additional nights of recovery sleep. Total sleep opportunity on SD nights was 4 hrs, and on recovery/sleep control (SC) nights was 8 hrs. Light exposure, ambient temperature, food and fluid intake, and physical activity were controlled. Self-reported fatigue and pain, pain sensitivity, and habituation were collected throughout. Data were analyzed with linear mixed models. Results: For women but not men, fatigue in response to SD recovered incompletely starting after the 2 nd sleep disruption-recovery cycle and remained elevated after the final 3 recovery nights in women ( p <.05). Additionally, women became more sensitive to pressure pain in response to SD (p<.001) with incomplete return to baseline after the final 3 recovery nights. Whereas men habituated to cold pain across SC and even more so across SD ( p =.045 Day, p =.021), women did not habituate. Conclusion: These results indicate that incomplete recovery in both fatigue and pressure pain, alongside a lack of habituation to cold pain, in response to sleep disruption may explain the common co-occurrence of insomnia, fatigue, and pain observed as more prevalent in women. Support: NIH/NINDS R01-NS091177; NIH/National Center for Research Resources UL1-RR02758 and M01-RR01032 to the Harvard Clinical and Translational Science Center.